Olfactory performance is predicted by individual sex-atypicality, but not sexual orientation - Nováková, Lenka; Varella Valentová, Jaroslava; Havlíček, Jan (PloS one, 2013)
Many previous studies have reported robust sex differences in olfactory perception. However, both men and women can be expected to vary in the degree to which they exhibit olfactory performance considered typical of their own or the opposite sex. Sex-atypicality is often described in terms of childhood gender nonconformity, which, however, is not a perfect correlate of non-heterosexual orientation. Here we explored intrasexual variability in psychophysical olfactory performance in a sample of 156 individuals (83 non-heterosexual) and found the lowest odor identification scores in heterosexual men. However, when childhood gender nonconformity was entered in the model along with sexual orientation, better odor identification scores were exhibited by gender-nonconforming men, and greater olfactory sensitivity by gender-conforming women, irrespective of their sexual orientation. Thus, sex-atypicality, but not sexual orientation predicts olfactory performance, and we propose that this might not be limited to olfaction, but represent a more general phenomenon.
Keywords: homosexualita ženská; heterosexualita; Olfactory Perception; Homosexuality, Female; sexuální chování; Odorants; sexuální faktory; průzkumy a dotazníky; mužské pohlaví; Adult; homosexualita mužská; genderová identita; Heterosexuality; Sexual Behavior; ženské pohlaví; čichová percepce; Humans; Sex Factors; Sex Characteristics; Homosexuality, Male; Surveys and Questionnaires; dospělí; odoranty; pohlavní dimorfismus; Female; lidé; Male; Gender Identity